Genetic variation in ACE A2350G: association with reduction in fasting blood glucose after fluoxetine therapy in depressed patients - Negar Firouzabadi; Mohammad Reza Hooshangi Shayesteh; Nasrollah Erfani; Ali Alavi Shoushtari (Shiraz University of Medical Sciences, 2016)
Various studies have shown that genetic factors contribute substantially to the development and progression of diabetes. Renin-angiotensin system has long been proven to have a major role in cardiovascular physiology and pathology. Its major product Angiotensin II (Ang II) with pro oxidant properties has shown to predict the future risk of diabetes. Fluoxetine, a drug of choice in management of depression, was observed to reduce fasting blood sugar (FBS). In the present study, six common polymorphisms of genes encoding for RAS components were determined in DNAs extracted from venous blood of 100newly diagnosed depressed individuals taking 12 weeks of fluoxetine. Blood samples were collected prior and after the period of treatment in order to measure FBS. Our results indicate that carriers of GG genotype of ACE A2350G showed significantly lower FBS levels after fluoxetine treatment (P=0.043). On the other hand haplotype analysis designate a significant association between DTG carriers of ACE I/D, A-240T and A2350G (P=0.001) and reduced FBS levels. In conclusion, this study supports the hypothesis that RAS genetic variations affect blood glucose after a course of treatment in Iranian population with depression